KETERAMPILAN INKUIRI SISWA SMA DALAM MODEL PEMBELAJARAN INKUIRI BERBANTUAN VIRTUAL LABORATORY - Desy Dwi Karmila; Supeno Supeno; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract The teaching and learning process of science, especially physics, will be meaningful if the teaching and learning process is appropriate with the nature of science, it means that learning physics is not only through the collection of facts, principles, laws, and theories, but also involves the process of knowledge is obtained. The learning process is beneficial in the skills of the students’ inquiry, such as increasing social interaction between the students, giving the students the opportunity to do activities directly, guiding the students to develop scientific vocabulary, encouraging the development of problem solving skills, helping cognitive growth, improving attitudes towards science, and helping the students to build mental images from new ideas. The type of research used is experimental research. The research design used nonequivalent control group design. In determining the place of research using the purposive sampling area method. The research was conducted in SMAN 1 Purwoharjo in the even semester of the 2018/2019 academic year. The competencies and indicators of inquiry skills that will be used are: (1) observation (2) investigation (3) exploration (4) skills to find something new. The analysis technique used the Independent Sample T-Test using the SPSS version 23 program, which is used to analyze the effect of the virtual laboratory assisted inquiry model on the skills of high school student inquiry. Based on the results of this research, it is known that the virtual laboratory inquiry model significantly have effects to the skills of high school students’ inquiry. Keywords: inquiry learning model, virtual laboratory, inquiry skill